3d integration in VLSI circuits implementation technologies and applications - Sakuma, Katsuyuki (Devices, circuits, & systems, 2016)
Currently, the term 3D integration includes a wide variety of different integration methods, such as 2.5-dimensional (2.5D) interposer-based integration, 3D integrated circuits (3D ICs), 3D systems-in-package (SiP), 3D heterogeneous integration, and monolithic 3D ICs. To provide readers with state-of-the-art information on 3D integration research and technology developments, each chapter has been contributed by some of the world's leading scientists and experts from academia, research institutes, and industry from around the globe.